A Study on Techniques for Handling Transmission Error of IPV6 Packets over Fmer Optic Links - Budiarto, Rahmat; Ramadass, Ureswaran (Universiti Sains Malaysia, 2010)
Problem identification of the existing error control mechanism is very important to find out a new suitable design to solve the problem of ineffective error control.The identification results become main basic of designing a new mechanism.Hence, the design obtained truly solves the problem accurately.